A key to the microfilariae of the genus litomosoides (phylum nematoda), endoparasites from Colombia bats (1999)
A key is provided for the identification of eight species of microfilariae of Litomosoides (Filarioidea: Onchocercidae) found in the blood of 85 Colombian bats. Eleven new host records for Colombia are reported for L. brasiliensis, L. caliensis, L. colombiensis, L. guiterasi and L. molossi.